Gross Anatomical Studies on the Adrenal Gland in Prenatal Goat (Capra hircus) - Pathak,Satish K (Sociedad Chilena de Anatomía, 2014)
The present study was conducted on the 24 healthy and normal embryos/foeti of non- descript goat (Capra hircus) varying from day old to 150 days of gestation. The embryo/foeti were assigned into three groups according to their gestational ages; Groups I (0-50 days), II (51-100 days) and III (101-till term). At 38 days of gestation the primordia of right and left adrenal gland were observed as a pea shaped spherical swelling located just cranial to the respective metanephros. Biometrical studies revealed the increase in the all parameters of the adrenal gland with the advancement of age. Adrenal glands were harvested first grossly at 50 days of gestation.